Aplikasi Pemupukan Terhadap Pertumbuhan Tanaman Aren Genjah (Arenga pinnata) dan Tanaman Kakao (Theobroma cacao) Pada Penanaman Sistem Jalur - Yetti Elidar (Agrifarm : Jurnal Ilmu Pertanian, 2018)
Planting with a lane system in palm sugar and cacao plants is a technique of plantation cultivation that aims at soil conservation and microenvironment. Plant cultivation in the field needs to get a supply of fertilizer to increase crop productivity. This study aims to determine the effect of giving SP-36 and KCl fertilizer to the best growth of sugar palm and cacao plants in the planting of path systems. The research was conducted on land in Badak Mekar Village, Muara Badak District, Kutai Kartanegara Regency, East Kalimantan. The research method used a Randomized Block Design (RBD) and repeated 4 times. Factorial experiments consisted of 2 factors, as the first factor was SP-36 fertilizer (p) consisting of 3 levels: p0 = 0 kg plant-1 (control); p1 = 0.25 kg of plant-1; p2 = 0.5 kg of plant-1. The second factor was KCl (k) fertilizer consisting of 3 levels: k0 = 0 kg plant-1 (control); k1 = 0.25 kg of plant-1; k2 = 0.5 kg of plant-1. The variables observed included: (1) Arenaceous plants: increase in caudal circumference, increase in the fifth midrib length, increase in the number of midribs, increase in number of leaflets on the fifth midrib and (2) Cocoa plants: increase in plant height, increase in stem circumference, the number of cocoa fruits, the intensity of pest and disease attacks on cocoa fruit. Observations on each variable were carried out at 3 and 6 months after treatment (mat). Data were analyzed by variance and if there were significant differences, it was followed by the Smallest Significant Difference Test (LSD) at the level of 5%. The results of the SP-36 fertilizer treatment showed very significant differences in all observation variables in early maturing palm trees and aged 3 bsp and 6 bsp cacao plants. The treatment of SP-36 fertilizer at a dose of 0.5 kg plant-1 (p2) gave the best growth of early maturing sugar palm plant 6 in the increase of the fifth midrib length, increase in bulb circumference, increase the number of midribs and increase the number of leaflets on the fifth midrib - each 137.17 cm, 25.58 cm, 3.25 strands and 39.08 strands. Likewise in the age of 6 bsp cocoa plants SP-36 fertilizer with a dose of 0.5 kg plant-1 (p2) gave the best growth in plant height increase, increase in stem circumference and number of cocoa fruit, each 18.92 cm, 8.25 cm and 25.25 pieces. The treatment of KCl fertilizer and the interaction between SP-36 and KCl fertilizers showed no significant difference in all observation variables in early maturing and cacao plants. Observations of pest and disease attacks on cocoa fruit with the intensity of pest attacks 0.00-23.47% were included in the category of minor damage and the intensity of disease attacks 0.00-66.30% which fall into the category of moderate damage.